Inhibitory Effect of Boesenbergia rotunda Rhizome Ethanol Extract on Porphyromonas gingivalis Lipopolysaccharide - Putri Annur Oktarinda; Melanie Hendriaty (Greenation Publisher & Yayasan Global Research National, 2026)
Periodontal disease is an inflammatory condition that damages periodontal supporting tissues and is closely associated with microbial biofilm. Porphyromonas gingivalis is a major periodontal pathogen, and its lipopolysaccharide (LPS) contributes to host inflammatory responses and tissue destruction. This study aimed to determine the inhibitory effect of Boesenbergia rotunda rhizome ethanol extract on P. gingivalis LPS. A laboratory experimental study with a posttest-only control design was conducted in vitro. P. gingivalis ATCC 33277 was treated with B. rotunda extract at 10, 20, and 40 µg/mL, chlorhexidine 0.2% as the positive control, and distilled water as the negative control. LPS concentration was measured using ELISA and analyzed with Shapiro-Wilk, Kruskal-Wallis, and Mann-Whitney tests. The lowest LPS concentration was observed in the 40 µg/mL extract group, with a mean of 2.33 ± 1.46 ng/mL. The Kruskal-Wallis test showed a significant difference among groups (p = 0.001). B. rotunda rhizome ethanol extract inhibited P. gingivalis LPS, with 40 µg/mL showing the strongest effect.